The influence of learning media and learning interests on student learning outcomes - Eli Yuliansih; Yasir Arafat; Achmad Wahidy (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
The purpose of this study was to determine the Effect of Learning Media and Learning Interests on Student Learning Outcomes in Man 1 MusiBanyuasin.  Students of Man 1 Musi Banyuasin were the object of this study. The sample was conducted on 87 students of Man 1 MusiBanyuasin. The sampling technique used purposive sampling in which the respondents were some of the students of Man 1 Musi Banyuasin. The data collected by distributing questionnaires using a 5-point Likert scale to measure 73 statement items. The analysis technique used was multiple linear regression analysis. The results showed that first, students' interest in learning and the use of learning media simultaneously had a significant effect on student learning outcomes. Second, student learning interest had a partial and significant impact on student learning outcomes. Third, the use of learning media had a partial and significant impact on student learning outcomes.